2001
DOI: 10.1128/aac.45.11.3175-3181.2001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antimalarial Synergy between Bestatin and Endoprotease Inhibitors Using Statistical Response-Surface Modelling

Abstract: The pathway of hemoglobin degradation by erythrocytic stages of the human malarial parasite Plasmodium falciparum involves initial cleavages of globin chains, catalyzed by several endoproteases, followed by liberation of amino acids from the resulting peptides, probably by aminopeptidases. This pathway is considered a promising chemotherapeutic target, especially in view of the antimalarial synergy observed between inhibitors of aspartyl and cysteine endoproteases. We have applied response-surface modelling to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…2), indicating 312 that the effects of the haemoglobinase inhibitors on protein synthesis were unlikely to be 313 merely secondary consequences of growth inhibition by some other mechanism. 314 315 Plasmepsin and falcipain inhibitors have been reported to display strong synergistic 316 effects on growth of P. falciparum [26, [45][46][47]. The data in Fig.…”
mentioning
confidence: 66%
“…2), indicating 312 that the effects of the haemoglobinase inhibitors on protein synthesis were unlikely to be 313 merely secondary consequences of growth inhibition by some other mechanism. 314 315 Plasmepsin and falcipain inhibitors have been reported to display strong synergistic 316 effects on growth of P. falciparum [26, [45][46][47]. The data in Fig.…”
mentioning
confidence: 66%
“…In addition, information gleaned from our preliminary SAR and crystallography efforts may provide a jumping off point for future medicinal chemistry efforts against both enzymes. Our data here suggest that combination therapy involving endopeptidase inhibitors, such as those for falcipains, and PfA-M1-specific inhibitors might provide an opportunity for a synergistic drug combination (52). Ultimately, this strategy may represent a good way to reduce the chance of parasite resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that the aminopeptidase inhibitor bestatin, an antibiotic and natural analogue of the dipeptide Phe-Leu derived from the fungus Streptomyces olivoretticul, prevents P. falciparum malaria growth in culture (13,14). More recently, it was shown not only that synthetic phosphinate dipeptide analogues that inhibit metallo-aminopeptidases prevented the growth of wildtype and the chloroquine-resistant parasites in culture but also that one compound, hPheP[CH 2 ]Phe (termed compound 4, Co4), reduced a murine infection of Plasmodium chabaudi chabaudi by 92% compared with controls (15,16).…”
mentioning
confidence: 99%